2014
DOI: 10.1007/s10664-014-9352-6
|View full text |Cite
|
Sign up to set email alerts
|

Empirical assessment of machine learning-based malware detectors for Android

Abstract: To address the issue of malware detection through large sets of applications, researchers have recently started to investigate the capabilities of machine-learning techniques for proposing effective approaches. So far, several promising results were recorded in the literature, many approaches being assessed with what we call in the lab validation scenarios. This paper revisits the purpose of malware detection to discuss whether such in the lab validation scenarios provide reliable indications on the performanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
131
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 117 publications
(138 citation statements)
references
References 27 publications
2
131
0
Order By: Relevance
“…We found that the performance decreases (but still with Fmeasure above 0.86) with the ratio of malware in the set. Such a finding was already shown in Allix et al's large scale empirical study with a different feature set [2]. RQ3:PCLs constitute good features for discriminating malicious apps from benign apps in a Machine learning-based malware detection scheme.…”
Section: Malware Identificationmentioning
confidence: 56%
See 3 more Smart Citations
“…We found that the performance decreases (but still with Fmeasure above 0.86) with the ratio of malware in the set. Such a finding was already shown in Allix et al's large scale empirical study with a different feature set [2]. RQ3:PCLs constitute good features for discriminating malicious apps from benign apps in a Machine learning-based malware detection scheme.…”
Section: Malware Identificationmentioning
confidence: 56%
“…The size of training sets and the parameters we use (e.g., malware/goodware ratio) take different values that appear to be unjustified since, as shown in [2], no survey has determined the appropriate values for malware detection. However, our results show the same trends of that shown in [2].…”
Section: Threats To Validitymentioning
confidence: 99%
See 2 more Smart Citations
“…It is thus obvious that the performance of the detector is tightly dependent on the quality of the training dataset. Previous works have even shown that the accuracy of such detectors can be degraded by orders of magnitude if the training data is faulty [26]. Following these ndings, one can easily infer that it is also possible to articially improve the performance of malware detectors by selecting a ground truth that splits around malware corner cases.…”
Section: Introductionmentioning
confidence: 88%